2021
DOI: 10.5114/ait.2021.103513
|View full text |Cite
|
Sign up to set email alerts
|

A sudden presentation of abdominal compartment syndrome

Abstract: LeTTeRs TO The eDITOR Dear editor, Abdominal compartment syndrome (ACs) is defined as sustained intraabdominal pressure (IAP) exceeding 20 mm hg, which causes end-organ damage due to impaired tissue perfusion, as with other compartment syndromes [1, 2]. This dysfunction can extend beyond the abdomen to other organs like the heart and lungs. ACs is most commonly caused by trauma or surgery to the abdomen. It is characterised by interstitial oedema, which can be exacerbated by large fluid shifts during massive t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…A non-physiological stretch of part of the detrusor shifts the length-tension curve to a higher tension, thereby results in a higher pressure, in response to lling volume [28]. This proposal is supported by a clinical study showing a sudden onset bladder compression results in an abruptly elevated intra-vesical pressure in patients [29] and a preclinical study demonstrated modi ed bladder geometry that abolishes physiological distension results in decreased bladder compliance in rabbits [30]. Notably, after correcting anatomical abnormalities in POP patients, RSCP relieved the restriction of bladder expansion coming from the prolapsed organ.…”
Section: Discussionmentioning
confidence: 97%
“…A non-physiological stretch of part of the detrusor shifts the length-tension curve to a higher tension, thereby results in a higher pressure, in response to lling volume [28]. This proposal is supported by a clinical study showing a sudden onset bladder compression results in an abruptly elevated intra-vesical pressure in patients [29] and a preclinical study demonstrated modi ed bladder geometry that abolishes physiological distension results in decreased bladder compliance in rabbits [30]. Notably, after correcting anatomical abnormalities in POP patients, RSCP relieved the restriction of bladder expansion coming from the prolapsed organ.…”
Section: Discussionmentioning
confidence: 97%